Assimilation in Childrenâ€™s Connected Speech in â€œHiHo Kidsâ€ YouTube Videos - Swari, Radha Andhra (Jurnal Budaya, 2020)
AbstractThis study investigated the types of assimilation that occur in childrenâ€™s connected speech in selected â€œHiHo Kidsâ€ videos. Descriptive qualitative method was applied in this study. The source of the data were six videos from â€œHiHo Kidsâ€ YouTube channel, particularly the ones from the section of â€œKids Tryâ€ that were uploaded in September to November 2019. The data collection process involves watching and transcribing the videos manually. Two research instruments, namely the official website of Oxford Learnerâ€™s Dictionary (https://oxfordlearnersdictionaries.com) and IPA transcription website (https://ipa.typeit.org/), were used for this study, in order to check the correct pronunciation of North American (NAmE) accent, as well as typing the phonetic symbols. In terms of data analysis, the researchers identified the findings based on the theories of assimilation types by Roach (1998) and Crystal (2008). The results revealed that regressive assimilation is the most prevalent type that occurs in childrenâ€™s connected speech in the selected videos, though progressive and coalescent assimilation also occur in certain cases.Keywords: assimilation, childrenâ€™s connected speech, HiHo Kids videosÂ Abstrak Studi ini menyelidiki jenis asimilasi yang terjadi pada ujaran terhubung anak-anak dalam video "HiHo Kids". Metode deskriptif kualitatif diterapkan dalam penelitian ini. Sumber datanya adalah enam video dari channel YouTube â€œHiHo Kidsâ€, khususnya dari bagian â€œKids Tryâ€ yang diunggah pada September hingga November 2019. Proses pengumpulan data meliputi menonton dan mentranskripsikan video tersebut secara manual. Dua instrumen penelitian, yaitu situs resmi Oxford Learner's Dictionary (https://oxfordlearnersdictionaries.com) dan situs transkripsi IPA (https://ipa.typeit.org/), digunakan untuk penelitian ini, guna memeriksa kebenarannya. pengucapan aksen Amerika Utara (NAmE), serta mengetik symbol fonetik. Dalam hal analisis data, peneliti mengidentifikasi temuan berdasarkan teori tipe asimilasi menurut Roach (1998) dan Crystal (2008). Hasilnya menunjukkan bahwa asimilasi regresif adalah jenis yang paling umum terjadi pada ujaran terhubung anak-anak di video yang dipilih, meskipun asimilasi progresif dan penggabungan juga terjadi dalam kasus tertentu.Kata kunci: asimilasi, percakapan anak-anak, video HiHo KidsÂ